Rzymska idea samobójstwa - Sapota, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
The aim of this article is to elucidate Iuv. 8. 83-84 where the Roman concept of honorable suicide is alluded to. The author presents ideological background of mors Romana and compares the Roman idea of voluntary self-killing with Greek views on the subject.

Juvenal 8.83-4: summum crede nefas animam praeferre pudori / et propter vitam vivendi perdere causas! is analysed in confrontation with ethical theory (Seneca, Pliny the Elder, Pliny the Younger) and historical data (Tacitus, Livy) regarding the phenomenon of suicides committed during the period when the Roman Republic was in agony and the imperial regime was being established. The opinions of the cited Roman authors bring to mind an idea of virtus Romana, which in those times prescribed that a citizen should choose to die, if keeping on living would put his honor at risk. Being unable to preserve one’s honor intact and yet clinging to living was deemed unworthy of a free man.
The Roman views on suicide
Keywords: Juvenal; suicide; virtus Romana